(untitled) (International Journal of Engineering and Computer Science, 2019)
This paper presents a new mesh generation method for a simply connected curved domain of a planar region whose boundary is defined by one or more equations in polar coordinates and a positive integer parameter ‘n’, ( n=2,4,6,8,......etc.) for specification of the wished degree of refinement.We first decompose this curved domain into simple sub regions in the shape of curved triangles. These simple regions are then triangulated to generate a fine mesh of linear triangles in the interior and curved triangles or linear triangles near to the boundary of curved domain.These simple regions are then triangulated to create 6-node triangles by inserting midside nodes to these triangles. Each isolated 6-node triangle is then split into four triangles according to the usual scheme, that is, by using straight lines to join the midside nodes. To preserve the mesh conformity a similar procedure is also applied to every triangle of the domain to fully discretize the given starshaped curved domain or cracked convex curved domains into all triangles,and quadrilaterals